Multiplex networks : basic formalism and structural properties /: basic formalism and structural properties. ([2018]) - Cozzo, Emanuele; Arruda, Guilherme Ferraz de; Rodrigues, Francisco Aparecido; Moreno, Yamir
No abstract available